Desempenho produtivo de animais de quatro raças zebuínas, abatidos em três estádios de maturidade. 1. Ganho de peso e de carcaça e eficiência de ganho - Jorge, André Mendes [UNESP]; De Alencar Fontes, Carlos Augusto; Paulino, Mário Fonseca; Gomes Jr., Paulo; Ferreira, Juliana Nardelli (My University, 1998)
This research was conducted to evaluate the productive performance (live weight gain and carcass weight gain and gain efficiency) of animals from four zebu breed slaughtered in three maturity stages. Thirty-six bulls from Gyr, Guzera, Mocho Tabapuã and Nellore with twenty-four months of average age and average initial live weight of 357.6, 362.0, 368.6 and 376.4 kg, respectively, were used. The bulls, from each breed, were randomly assigned to individual pens and were full-fed a diet containing 50% concentrate (DM basis) and distributed to three category (1, 2 and 3) of slaughter weights. The bulls from category 1, 2 and 3 were slaughtered when reached the individual live weight of 405, 450 and 500 kg, respectively. At slaughter the empty body weight was determined. The Nellore breed bulls showed greater average empty body weight gain and carcass gain in relation to the other breeds, which did not differ among themselves. There were no differences among breeds regarding to feed efficiency (empty body weight gain efficiency and carcass gain efficiency per unit of metabolizable energy intake). The slaughter weight did not influence the empty body weight gain and carcass gain, but animals slaughtered at higher slaughter weights showed lower gain efficiency and spent more time in feedlot.
Productive performance of animals from four zebu breed, slaughtered at three stages of maturity. 1. Weight gain, carcass gain and gain efficiency
Keywords: Beef cattle; Carcass efficiency gain; Carcass gain; Weight efficiency gain; Weight gain; Zebu cattle